2019
DOI: 10.3168/jds.2018-15797
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: Completeness of reporting of experiments: REFLECTing on a year of animal trials in the Journal of Dairy Science

Abstract: Reproducibility is an essential element of the scientific process, and it requires clear and complete reporting of study design, conduct, and analysis. In the human and animal health literature, incomplete reporting is associated with biased effect estimates. Moreover, incomplete reporting precludes knowledge synthesis and undervalues the resources allocated to the primary research. The Reporting Guidelines for Randomized Controlled Trials for Livestock and Food Safety (REFLECT) statement, published in 2010, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…There is evidence that reporting of randomization has improved since the publication of reporting guidelines such as the REFLECT statement (Totton et al ., 2018). However, reporting specific to dairy science revealed that although 104 of a sample of 137 trials published in 2017 reported random allocation to study group, only seven reported the method of randomization (Winder et al ., 2019). Assumptions for many statistical methods rely on interchangeable groups, and failure to randomize has been shown to be associated with exaggerated treatment effects (Burns and O'Connor, 2008; Sargeant et al ., 2009 a ; Brace et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that reporting of randomization has improved since the publication of reporting guidelines such as the REFLECT statement (Totton et al ., 2018). However, reporting specific to dairy science revealed that although 104 of a sample of 137 trials published in 2017 reported random allocation to study group, only seven reported the method of randomization (Winder et al ., 2019). Assumptions for many statistical methods rely on interchangeable groups, and failure to randomize has been shown to be associated with exaggerated treatment effects (Burns and O'Connor, 2008; Sargeant et al ., 2009 a ; Brace et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A lack of reporting key design features is consistent with recent evaluations of animal health research (Totton et al, 2018;Winder et al, 2019), and a lack of reporting has been associated with exaggerated treatment effects (Wellman and O'Connor, 2007;Sargeant et al, 2009aSargeant et al, , 2009b. Not only do deficiencies in The upper right-hand section of the table represents the risk ratio between the numerator (upper left treatment) and denominator (lower right treatment).…”
Section: Limitations Of the Body Of Evidencementioning
confidence: 79%
“…In this review, although there were trials where allocation to the intervention group was not random, the more common issue was trials where the authors referred to allocation as ‘random,’ but did not provide a description as to how the allocation sequence was generated, counter to recommended reporting standards (Schulz et al ., 2010; O'Connor et al ., 2010 a ). Failure to report key features related to the potential for bias were also noted in this review, which is consistent with other publications which have evaluated the quality of reporting in livestock trials (Wellman and O'Connor, 2007; Burns and O'Connor, 2008; Sargeant et al ., 2009 a , 2009 b ; Brace et al ., 2010; Winder et al ., 2019). Some study characteristics were also not well reported in the trials included in this review, such as month of study conduct and location of the study.…”
Section: Discussionmentioning
confidence: 99%